Validation of the Multi-Dimensional Student Perceptions of School Questionnaire (MSPSQ): Early findings and next steps - Macdonald, Mary-anne; Gringart, Eyal (The Australian Journal of Indigenous Education, 2022)
Research in Indigenous and non-Indigenous education in Australia over the last two decades has begun to turn towards quantitative methods of understanding various factors affecting student outcomes. The current article presents a new measurement instrument, the Multi-Dimensional Student Perceptions of School Questionnaire (MSPSQ), validated with a moderate-sized sample of secondary students in Western Australia (Indigenous: n = 244; non-Indigenous: n = 258; not stated: n = 34). The MSPSQ aimed to measure student perceptions of select experiences within the family, community and school which may factor in school engagement and beliefs regarding normative education behaviour and likely outcomes. Exploratory factor analysis indicated that the 46 scalar items in the MSPSQ adequately reflected 12 underlying constructs for the given sample. The MSPSQ was found to have robust total internal consistency (α = 0.85), as well as good measures of Cronbach’s alpha (α > 0.7) on six constructs of self-reported student experiences: Positive school culture, Student self-efficacy, Pathway development, Provision of study assistance, Family support, and Peer support. Five other constructs had moderate internal consistency (α > 0.6). These were Promotion of Indigenous culture, Access to a suitable study environment, Future aspirations, School importance, and Perceived benefit of education.